Functionalized carbon nanotubes for hydrocarbon removal from water. Issue 2 (April 2020) - Al-Jammal, Noor; Abdullah, Thamer Adnan; Juzsakova, Tatjána; Zsirka, Balázs; Cretescu, Igor; Vágvölgyi, Veronika; Sebestyén, Viktor; Le Phuoc, Cuong; Rasheed, Rashed T.; Domokos, Endre
Abstract: This study aims to develop advanced sorbents for the removal of hydrocarbons from surface waters. The microemulsion method was implemented to modify the surface structure of multiwalled carbon nanotube (MWCNTs) by attaching a hydrocarbon tail on its surface. The structural and surface chemistry properties of the prepared adsorbents were studied by different surface analytical techniques such as Brunauer-Emmett-Teller (BET) method, X-Ray diffraction (XRD), Raman-spectroscopy, Fourier-transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TG). Scanning electron microscopy (SEM) was used to study the microstructure and morphology of the samples. Different model hydrocarbon compounds were used for this investigation. The hydrocarbon removal efficiencies of the unmodified and functionalized sorbents were studied by using total organic carbon analyzer (TOC), gas chromatography (GC), and UV–vis spectroscopy (UV–vis) techniques. Surface chemistry studies over raw and microemulsified multiwalled carbon nanotubes (μEMWCNT) revealed that that microemulsion functionalization resulted in changes in the CH bending vibrations of the functionalized MWCNTs as compared to the raw MWCNTs, demonstrating the existence of intermolecular CH-π interactions between the carbon nanotubes and lauric/miristic acid. The experimental results revealed that microemulsion technique as a type of surface functionalization solved one main issue regarding MWCNTs modification as it proved to have a beneficial effect on MWCNTs' hydrophobic properties without the need for additional functionalization and substitution steps to attach hydrocarbon side chains. Using kerosene as a hydrocarbon model mixture, compared with raw MWCNTs, the maximum adsorption capacity of μMWCNTs increased by 63.5 %. Additionally, the outcomes indicated that the n-octane adsorption capacities over μEMWCNTs reached 6.07 g/g. The kinetic studies demonstrated that the adsorption process over μMWCNTs could be well described by the pseudo-second-order model with a high correlation coefficient.